How well are women represented at the AEA meeting? A study of the 1985 - 2010 programs - Rosemary Cunningham; Madeline Zavodny (Institute for the Study of Labor (IZA), 2012)
The proportion female in the economics profession in the U.S. has been low historically compared with other disciplines. Although the percentage of Ph.D. degrees awarded to women and the representation of women on faculties have increased over time, economics still lags many other fields. Previous research has documented gender gaps in tenure, promotion and publication, some of which have narrowed over time. This study examines another aspect of women's representation within the economics profession: their participation in a session at the American Economic Association annual meeting. We examine the gender of participants on the program at the 1985-2010 meetings to determine how women's participation at this important venue has changed over the past 25 years. The results show that women's participation has increased over time, particularly since 2002. However, women appear to be underrepresented on the program relative to other measures of their representation in the profession.
urn:nbn:de:101:1-201305294507
Keywords: A1; 330; women in economics; economics profession; academic labor market; Ökonomen; Frauen; Wirtschaftsforschung; Geschlecht; USA